Pelvic Desmoid Tumor: A Rare Case with Difficult Diagnosis and Treatment - Mariana Ormonde; Despoina Argyropoulou; Cândida Lourenço; João Bastos; Ana Quintas (Case Reports in Obstetrics and Gynecology)
Desmoid tumors are rare benign neoplasms, with locally aggressive characteristics. Ongoing or previous pregnancy, antecedent trauma, and familial adenomatous polyposis are known risk factors. Still, the majority of cases are sporadic and its etiology is still unknown. These tumors may occur in any body site, but retroperitoneal and pelvic desmoid tumors are extremely rare. Nonspecific clinical and radiological findings lead to erroneous diagnosis in 50% of patients before surgery. We present a case of a young multiparous female with a deep infiltrative lesion adherent to the right pelvic sidewall leading to severe right hydroureteronephrosis and ipsilateral loss of renal function. Although deep endometriosis was suspected, malignancy features could not be excluded by imaging studies. The patient underwent an exploratory laparotomy for definite diagnosis and treatment, which led to right nephrectomy, hysterectomy, and right oophorectomy because of deep infiltration and difficult dissection. Definite histologic diagnosis revealed the presence of a pelvic desmoid tumor. Positive margins were encountered but, until this moment, no disease relapse occurred.